GeoInfographic design of the multi-spatiality of borders: A case study of epidemic prevention and control in Ruili, China. (May 2023) - Jiang, Ziwei; Tang, Xi; Zhang, Hong
We live in a world of borders, which influence our perception and movement. Traditional mapping techniques show limitations as borders have become shifting and complex, and borders' multi-scale and multi-spatial properties have been strengthened significantly. To fill the knowledge gap, we explored the multi-spatiality of borders and provided approaches for border symbol design and visualization by taking the coronavirus-hit border city, Ruili, China, as an example. This work could shed light on multi-spatial geographic visualization and policy-making.